THE DIFFERENCE IN LEARNING OUTCOMES OF CLASS V STUDENTS BEFORE AND AFTER COVID-19 AT PUBLIC ELEMENTARY SCHOOL 095256 PEMATANG BANDAR - Aulia Nanda, Ficha; Uribe, Martin; O Tambunan, Jubelando; Jusnita Samosir, Herna; Nur Asima Sidabutar, Melisa (International Conference on Health Science, Green Economics, Educational Review and Technology, 2020)
AbstractThis research was motivated by seeing student learning outcomes during the pandemic that had increased compared to learning outcomes before Covid-19 which was seen from the list of odd and even semester test scores for the 2019/2020 academic year at SD Negeri 095256 Pematang Bandar. The objectives of this study are (1) How Student Learning Outcomes before Covid-19 at SD Negeri 095256 Pematang Bandar; (2) What are the student learning outcomes during the covid-19 period at SD Negeri 095256 Pematang Bandar; (3) How are the differences in student learning outcomes before and after covid-19 in SD Negeri 095256 Pematang Bandar. This research is a type of quantitative research type of experiment. The sample used in this study were 27 students and the population used was all class V SD Negeri 095256 Pematang Bandar. Based on the results of the research data analysis, the test scores in this odd semester have a Liliefors value (L0 = 0.1694 > Lt = 0.173). The results of the test scores in this even semester have a Liliefors value (L0 = 0.14563 > Lt = 0.173). While the results of the homogeneity test using the F-test were obtained (Fcount < Ftable = 1.474 < 1.674). While the results of hypothesis testing using the t-test were obtained (tcount = 2.76 > ttable = 2.012). So it can be concluded that there is a significant difference between student learning outcomes before and after Covid-19 as seen from the List of T.P. Odd and Even Semester Exam Values. 2019/2020 In the Country 095256 Pematang Bandar.